Impact of riverbank erosion on riparian society: a micro-level study along the Ganga-Padma river in Samserganj C.D. Block of Murshidabad District, West Bengal - Saha, Pallab; Sahu, Abhay Sankar (Bulletin of Geography. Socio-economic Series, 2023)
Th e present paper is a micro-level study aimed at analyzing the impacts of riverbank erosion on riparian society. To fulfi ll the objective, the study has been carried out from two distinctive perspectives; viz. general outlooks and specifi c inquiry. For the general outlook, the Ganga-Padma river in its lower reach downstream of Farakka Barrage in Samserganj Community Development Block has been explored in terms of channel shift ing using multi-dated satellite images. For specifi c inquiry, the eff ects of riverbank erosion on society have been studied using primary data in two selected active bank-erosion-prone cadastral units. Th e results show that recurrent bank erosion has brought a drastic change in the social fabric and caused huge losses rendering riparian inhabitants quite vulnerable, since most of the people in the study units are dependent on land-based economy and belong to poor economic groups. Th ese situations necessitate signifi cant outside assistance. However, there is a signifi cant diff erence (χ2 = 10.85 at p<0.01) in terms of assistance received during the previous year between the two selected study units.